EPIGENOMICS: ROLE, APPROACHES AND APPLICATIONS IN PLANTS - P. K. Malhotra; G. Verma; G. S. Sidhu; N Duhan (Journal of Animal and Plant Sciences, 2020)
Epigenetic changes are caused due to change/activation of certain genes in DNA microstructure and not in DNA sequences. With continuous growth in existing knowledge about the mechanisms and potential role of epigenomics in plants, there is a lot of enthusiasm and eagerness about the prospective for three epigenetic information systems (EIS) viz. DNA methylation, Histone modification and RNA interference. The various genetic and biochemical approaches along with epigenomics will broaden our understanding of plant genomes and metabolic pathways. Insight into epigenomics can also help in improving strategies for better control over the transgene expression during development of transgenics. Although there were many studies about epigenetic modifications in previous decades, it is only through high-performing approaches and developments in bioinformatics technology that made possible to analyse this globally. Epigenomic information is important in understanding gene regulation during early stages of plant development, plants’ responses to the external stimulants and in natural variation for crop improvement. Therefore, the present review aims at discussing the role of epigenomics, the combination of approaches used and the applications of epigenomics in context to plants.
Keywords: Epigenomics; Arabidopsis; DNA methylation; siRNA; histone